Enantioselective Construction of Si‐Stereogenic Center via Rhodium‐Catalyzed Intermolecular Hydrosilylation of Alkene. Issue 71 (18th November 2020) - He, Tao; Liu, Li‐Chuan; Ma, Wen‐Peng; Li, Bin; Zhang, Qing‐Wei; He, Wei
Abstract: Catalytic, enantioselective synthesis of stereogenic silicon compounds remains a challenge. Herein, we report a rhodium‐catalyzed regio‐ and enantio‐selective intermolecular hydrosilylation of alkene with prochiral dihydrosilane. This new method features a simple catalytic system, mild reaction conditions and a wide functional group tolerance. Abstract : A rhodium‐catalyzed regio‐ and stereoselective hydrosilylation from prochiral dihydrosilane to terminal alkene is realized, which extends the limited success of asymmetric construction of Si‐stereogenic centers. The new reaction features simple conditions, a general substrate scope and excellent functional group compatibility.